Alterations and resilience of intestinal microbiota to increased water temperature are accompanied by the recovery of immune function in Nile tilapia - Zhenbing Wu; Qianqian Zhang; Xiehao Wang; Aihua Li (Scientific Reports)
Abstract In the context of ongoing global warming, fish, as aquatic ectotherms, are highly vulnerable to increased water temperature caused by climate change and extreme heatwaves because of their inability to maintain their body temperature. After prolonged coevolution, the intestinal microbiota has become an integral part of fish and plays a pivotal role in immunity and metabolism. To date, however, little is known about the effects of increased water temperature on the intestinal microbiota of fish, particularly the intestinal mucosa-associated microbiota. Here, we investigated the variation patterns of the intestinal microbiota and immune status in Nile tilapia (Oreochromis niloticus; 125.02 ± 4.55 g) under increased water temperature. The results showed that the microbial diversity, structure, dominant microbes, and predicted function of fish intestinal microbiota were resilient to low-level warming (increasing by 2 °C) but not to high-level warming (increasing by 8 °C) and that fish immune parameters (serum lysozyme content and bactericidal activity) recovered simultaneously. Notably, along with compromised immune function, short-term warming (7 days) drove a significant increase in the microbial richness and diversity of fish intestinal mucosae, in which the overgrowth of opportunistic pathogens such as Romboutsia ilealis, Escherichia–Shigella, Fusobacterium, Streptococcus, Acinetobacter, and Enterobacter inhibited the colonization of potential probiotics such as Cetobacterium, ultimately resulting in a significant reduction in metabolic pathways and a significant increase in the potentially pathogenic phenotype. After long-term warming (37 days), the above alterations disappeared in low-level warming but remained in high-level warming. Critically, long-term warming disrupted the network complexity and stability of the intestinal mucosa- and digesta-associated microbiota to different extents. Collectively, this study revealed that the alterations and resilience of intestinal microbiota to increased water temperature coincided with the recovery of immune function in fish. Our findings extend the understanding of how the intestinal microbiota in aquatic ectotherms respond to increased water temperature, providing important implications for harnessing the potential benefits of host-associated microorganisms to enhance their resilience to climate change.